Folding thermodynamics of PET-hydrolyzing enzyme Cut190 depending on Ca2+ concentration - Inaba, Satomi; Kamiya, Narutoshi; Bekker, Gert-Jan; Kawai, Fusako; Oda, Masayuki (Journal of thermal analysis and calorimetry, 2019)
The enzyme, cutinase from Saccharomonospora viridis AHK190 (Cut190), can hydrolyze the inner block of polyethylene terephthalate (PET). Cut190 has a unique feature that both its activity and thermal stability are increased upon Ca 2+ binding. In consideration of the glass transition temperature of PET, which is between 60 and 65 °C, the increased activity and thermal stability are of great interest to apply for PET bio-recycling. Our previous mutational analysis showed that the S226P/R228S mutant (Cut190*) has a higher activity and thermal stability than those of the wild type. In this study, we analyzed the folding thermodynamics of the inactive mutant of Cut190*, Cut190*S176A, using circular dichroism and differential scanning calorimetry. The results show that the denaturation temperature increases from 54 to 71 °C due to the addition of 250 mM Ca 2+ , in a Ca 2+ concentration-dependent manner. The increased thermal stability is mainly due to the increased enthalpy change, partially compensated by the increased entropy change. Based on the crystal structure of Cut190*S176A bound to Ca 2+ , molecular dynamics simulations were carried out to analyze the effects of Ca 2+ on the structural dynamics, showing that the Ca 2+ -bound structure fluctuated less than the Ca 2+ -free structure. Structural analysis indicates that Ca 2+ binding increases the intramolecular interactions of the enzyme, while decreasing its fluctuation, which are in good correlation with the experimental results of the folding thermodynamics.